RISK FACTORS AND PROGNOSIS OF NIDAL MORBIDITY OF TUBERCULOSITY (BY THE RESULTS OF DISPERSE ANALYSIS) - L. P. Aksyutina (Acta Biomedica Scientifica, 2012)
The author has carried out mathematical analysis which revealed the most significant risk factors of disease development in contact persons from nidi of tuberculosis infection, helped to define the degree of their influence on indices of nidal morbidity and to forecast development of epidemic process in epidemic nidi. The forecast table of morbidity in TB nidi was worked out and introduced. The use of this table will provide phthisiatricians and epidemiologists with the opportunity to carry out more qualitative antiepidemic measurements on the territory.